Valuing Play in Survivor: A Constructionist Approach to Multiplayer Games. Issue 4 (June 2020) - Carter, Marcus
The U.S. televised game Survivor is fascinating for the study of multiplayer games because the winner of a season of Survivor is not dictated by the rules. Instead, a "jury" of eliminated players vote for which of the remaining two to three contestants deserve to win the US1, 000, 000 prize, based entirely on their personal opinion. In this article, I present an analysis of Final Tribal Council, where this decision is made, revealing the key themes that influence this decision. I subsequently propose a social constructionist approach to understanding and researching multiplayer games as moral economies, where diverse types of play are given different values by players. I argue that this approach provides a useful theoretical framework for an integrated understanding of how both game and nongame elements work to influence player behavior and experience.